Spatial-temporal Evolution and Driving Factors of Ecological Environment Quality in Weihe River Basin Based on Remote Sensing Ecological Index - Wu Mengyue; Li Yu (E3S Web of Conferences)
As a critical component of northwestern China's ecological security barrier, it is of great significance to comprehensively and accurately grasp the changes of ecological environment quality and its influencing factors in Weihe River Basin, which is important for maintaining ecological security and ensuring sustainable development. Based on the Remote Sensing Ecological Index (RSEI), our study further explores the temporal and spatial evolution law and main driving factors of the ecological environment quality in Weihe River Basin from 2013 to 2023. A combination of analytical techniques, including trend analysis, variability assessment, and spatial interaction modeling, was used to evaluate ecological quality. Our analysed showed that the eco-environmental quality of Weihe River basin is generally fluctuating and rising, and the southern region is better than the northern region. Approximately 68.77% of the basin shows an upward trend, while 31.15% exhibits a decline. The average value of the variation coefficient of RSEI in Weihe River Basin is 0.211, showing a low fluctuation as a whole, and the low fluctuation changes are distributed in mountainous areas such as the Qinling mountains, Qianshan, Guanshan and Ziwuling mountains, mainly in areas with high ecosystem functions and relatively stable community structure. However, future projections suggest potential anti-sustainability trends, and the northern part of Huanxian County in Qingyang City and Jingning County in Ping liang City will face the risk of sustainable ecological environment degradation. Land use patterns were identified as the primary factor influencing spatial ecological variation. The research results of our study can provide actionable insights for formulating targeted ecological conservation strategies in the Weihe River Basin.